An antioxidant capacity of ethanol and ethyl acetate extracts of areca nut (Pinanga ceasia Blume), a plant endemic to Central Sulawesi - Elizabeth B.E Kristiani; Jeanelsin A.P Langgori (Sam Ratulangi University, 2023)
The purpose of this study to measure the antioxidant ability and content of phenolic and flavonoid compounds in ethanol and ethyl acetate extracts of areca nut (Pinanga ceasia Blume) taken from the Central Sulawesi region. The fruit were divided in the skin, seeds, and flesh. Samples were extracted by maceration using two types of solvents, namely ethanol and ethyl acetate. The parameters of the study were measured spectrophotometrically using specific reagents. The reagents used were DPPH for antioxidant activity test, Folin-Ciocalteu reagent for testing phenolic compound levels, and AlCl3 reagent for flavonoid level testing. The phenolic content of the ethanolic extract of the seeds and fruit flesh was in the range of 3,500 – 4,500 g equivalent of gallic acid/g extract, while the flavonoid content was in the range of 1,700 – 1,800 g equivalent of quercetin/g of extract. This value is much higher than other extracts in the range of 170 – 740 g bioactive equivalent/g extract. The antioxidant ability of the ethanol extract of the seeds and fruit pulp increased with increasing concentration of the extract, while the other extracts were relatively the same at all test concentrations. Keywords: antioxidant; flavonoid; maceration; phenolic; Pinanga ceasea Blume Kapasitas Antioksidan Ekstrak Etanol dan Etil Asetat Buah Pinang (Pinanga ceasia Blume), Tanaman Endemik Sulawesi Tengah ABSTRAK Penelitian ini bertujuan untuk untuk mengukur kemampuan antioksidan dan kadar senyawa fenolik dan flavonoid pada ekstrak etanol dan etil asetat buah pinang (Pinanga ceasia Blume) yang diambil dari daerah Sulawesi Tengah. Buah pinang dipisahkan bagian kulit, biji, dan daging buah. Sampel diekstraksi secara maserasi menggunakan dua jenis pelarut yaitu etanol dan etil asetat. Parameter uji diukur secara spektrofotometri menggunakan reagen spesifik. Reagen yang digunakan yaitu DPPH untuk uji aktivitas antioksidan, reagen Folin-ciocalteu untuk uji kadar senyawa fenolik, dan reagen AlCl3 untuk uji kadar flavonoid. Kadar fenolik ekstrak etanol biji dan daging buah pada kisaran 3.500 – 4.500 µg ekivalen asam galat/g ekstrak sedangkan flavonoid pada kisaran 1.700 – 1.800 µg ekivalen kuersetin/g ekstrak. Nilai tersebut jauh lebih tinggi dibanding ekstrak lain yang ada pada kisaran 170 – 740 µg ekivalen bioaktif/g ekstrak. Kemampuan antioksidan ekstrak etanol biji dan daging buah meningkat seiring meningkatnya konsentrasi ekstrak sedangkan ekstrak lain relative sama pada semua konsentrasi uji. Ekstrak etanol biji dan daging buah Pinanga ceasea Blume memiliki kadar flavonoid dan flavonoid lebih dari dari kulit buah. Kemampuan antioksidan ekstrak etanol biji dan daging buah Pinanga ceasea Blume lebih tinggi dibandingkan ekstrak lain. Kata kunci: Antioksidan; fenolik; flavonoid; maserasi; Pinanga ceasea Blume